Post-Decisional Regret in COVID-19 Vaccination Decisions: Psychological Correlates in a Greek-Speaking Sample - Marilena Mousoulidou; Loukia Taxitari; Andri Christodoulou; Nektarios-Alexandros Damianou (European Journal of Mental Health, 2026)
Introduction: Health-related decisions made during crises, such as the COVID-19 pandemic, can elicit strong emotional responses, including post-decisional regret. Understanding regret as a psychological response to such decisions may inform public health strategies and support individuals’ adjustment. Aim: This study examined post-decisional regret in COVID-19 vaccination decisions and its associations with decision-making styles, conspiracy mentality, and personality traits in a Greek-speaking sample. Methods: 325 adults (83.1% vaccinated, 16.9% unvaccinated) completed an online questionnaire assessing post-decisional regret, decision-making styles, conspiracy mentality, personality traits, and demographics. A pooled hierarchical regression examined associations between demographics, vaccination status, decision-making styles, conspiracy mentality, and postdecisional regret. Personality traits were examined separately using Spearman rank-order correlations due to multicollinearity among dimensions. Results: Vaccinated individuals reported significantly higher levels of regret than unvaccinated participants. The association between dependent decisionmaking and regret differed by vaccination status, with greater reliance on others associated with greater regret only among unvaccinated participants. A marginal interaction suggested that stronger conspiracy beliefs may be associated with greater regret among vaccinated participants. Personality traits showed modest associations with regret. Among vaccinated participants, higher scores on all Big Five traits were associated with greater regret, whereas among unvaccinated participants, higher Agreeableness was associated with lower regret. Conclusions: Post-decisional regret appears to be a psychologically meaningful response to health-related decisions and is associated with individual differences in decision-making styles and belief systems. These findings suggest that emotional responses may be an important aspect of health-related decision-making.